Highly conductive and flexible nano-structured carbon-based polymer nanocomposites with improved electromagnetic-interference-shielding performance. (25th October 2017) - Mondal, Subhadip; Ghosh, Sabyasachi; Ganguly, Sayan; Das, Poushali; Ravindren, Revathy; Sit, Subhashis; Chakraborty, Goutam; Das, Narayan Ch
Abstract: Widespread usage and development of electrical/electronic devices can create severe problems for various other devices and in our everyday lives due to harmful exposure to electromagnetic (EM) radiation. Herein, we report on the electromagnetic interference (EMI)-shielding performance of highly flexible and conductive chlorinated polyethylene (CPE)/carbon nanofiber (CNF) nanocomposites fabricated by a probe-sonication-assisted simple solution-mixing process. The dispersion of CNF nanofillers inside the CPE matrix has been studied by electron micrographs. This dispersion is reflected in the formation of continuous conductive networks at a low percolation-threshold value of 2.87 wt% and promising EMI-shielding performance of 41.5 dB for 25 wt% CNF in the X-band frequency (8.2–12.4 GHz). Such an intriguing performance mainly depends on the unique filler–filler or filler–polymer networks in CPE nanocomposites. In addition, the composite material displays a superior EMI efficiency of 47.5 dB for 2.0 mm thickness at 8.2 GHz. However, we have been encouraged by the promotion of highly flexible and lightweight CPE/CNF nanocomposite as a superior EMI shield, which can protect electronic devices against harm caused by EM radiation and offers an adaptable solution in advanced EMI-shield applications.